Delayed-Mode Quality Control of Oxygen, Nitrate, and pH Data on SOCCOM Biogeochemical Profiling Floats - Maurer, Tanya L.; Plant, Joshua N.; Johnson, Kenneth S. (Frontiers in Marine Science, 2021)
The Southern Ocean Carbon and Climate Observations and Modeling (SOCCOM) project has deployed 194 profiling floats equipped with biogeochemical (BGC) sensors, making it one of the largest contributors to global BGC-Argo. Post-deployment quality control of float-based oxygen, nitrate, and pH data is a crucial step in the processing and dissemination of such data, as in-situ chemical sensors remain in early stages of development. In-situ calibration of chemical sensors on profiling floats using atmospheric reanalysis and empirical algorithms can bring accuracy to within 3 µmol O2 kg-1, 0.5 µmol NO3- kg-1, and 0.007 pH units. Routine quality control efforts utilizing these methods can be conducted manually through visual inspection of data to assess sensor drifts and offsets, but more automated processes are preferred to support the growing number of BGC floats and reduce subjectivity among delayed-mode operators. Here we present a methodology and accompanying software designed to easily visualize float data against select reference datasets and assess quality control adjustments within a quantitative framework. The software is intended for global use and has been used successfully in the post-deployment calibration and quality control of over 250 BGC floats, including all floats within the SOCCOM array. Results from validation of the proposed methodology are also presented which help to verify the quality of the data adjustments through time.